Managing Dynamic Competition - Lewis, Tracy R; Yildirim, Huseyin (American Economic Review, 2002)
In many important high-technology markets, including software development, data processing, communications, aeronautics, and defense, suppliers learn through experience how to provide better service at lower cost. This paper examines how a buyer designs dynamic competition among rival suppliers to exploit learning economies while minimizing the costs of becoming locked in to one producer. Strategies for controlling dynamic competition include the handicapping of more efficient suppliers in procurement competitions, the protection and allocation of intellectual property, and the sharing of information among rival suppliers.